Advanced Photonics 2011
DOI: 10.1364/sl.2011.slwc2
|View full text |Cite
|
Sign up to set email alerts
|

Structural slow light can enhance Beer-Lambert absorption

Abstract: We experimentally demonstrate that structural slow light can enhance Beer-Lambert absorption. A 4-fold reduction of the group velocity induced by mere cavity effects has caused an increase of molecular absorption by 130%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…As detailed in section 3.2, the effect ofslow light on the nonlinear coupling coefficient γ can be summarized, approximately, as a c v 0 g 2 ( ) scaling. Interestingly, the linear absorption scales as c v 0 g ( ), which has been experimentally confirmed (see for instance [26]). In conclusion, not only the choice of the material, but also the geometry of the waveguide has a strong influence on the nonlinear dynamics.…”
Section: Slow-light Field Enhancement and Structural Slow-light As Op...supporting
confidence: 53%
“…As detailed in section 3.2, the effect ofslow light on the nonlinear coupling coefficient γ can be summarized, approximately, as a c v 0 g 2 ( ) scaling. Interestingly, the linear absorption scales as c v 0 g ( ), which has been experimentally confirmed (see for instance [26]). In conclusion, not only the choice of the material, but also the geometry of the waveguide has a strong influence on the nonlinear dynamics.…”
Section: Slow-light Field Enhancement and Structural Slow-light As Op...supporting
confidence: 53%
“…Current work has emphasized means of engineering PhC waveguides to minimize these sources of loss [23]. We also note that careful experimental studies performed by Thevenaz and coworkers have confirmed that linear absorption scales with the group index for structural but not material slow light [40,41].…”
Section: Structural Slow Lightmentioning
confidence: 68%
“…The experiment is designed so that the molecular absorption and the slow light generation are negligibly correlated and can be controlled independently, as it could be done with the material slow light experiment. The macroscopic cavity can be conveniently opened or closed to operate either in standard or in slow-light regime, leaving the absorbing fibre segment untouched 13 . Closing the cavity results in delayed propagation and longer effective optical path lengths according to the cavity round-trip loss.…”
Section: Experimental Test Using Structural Slow Lightmentioning
confidence: 99%